Cardiac calcification in acute intermittent porphyria - Tanmoy Ghatak; Afzal Azim; Arvind K Baronia; Banani Poddar (Wolters Kluwer Medknow Publications, 2011)
Aetiology of pericardial calcifications can be multifactorial. Tuberculosis has been reported as the most common cause. Other known causes include uraemia, asbestosis, post-traumatic or postoperative. We report a rare case of pericardial calcification seen in a patient with established acute intermittent porphyria. A direct causal relationship cannot be established between porphyria and pericardial calcification, but it may be due to deposition of the porphyrin in the pericardium.